Scientific activities Organizing Academician of O. Buhutskiy (second half of 1950 – beginning of XXІ century) - Pavlushko, Yu. I. (History of science and technology, 2014)
It was revealed that in the historical literature there is no comprehensive study of the life and work of the scientist, briefly and fragmentary reconstituted information on separate periods, in particular, the development of his scientific worldview, unsystematic scientific works. It was found that at the beginning of the scientific way to agro-economics, by focusing on strategically important issues of agriculture and applied-scientific fact, original results have been obtained by the scientists that extend the boundaries of the processes and phenomena that are investigated in agricultural science, enriched it and opened new research directions.